2014
DOI: 10.2134/agronj13.0378
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Pasture Bloat Can Be Eliminated by Intermixing with Newly‐Developed Sainfoin Population

Abstract: Pasture bloat is a major deterrent to the grazing of alfalfa (Medicago sativa L.) pastures by ruminants, despite the high growth rates that are obtainable. Sainfoin (Onobrychis viciifolia Scop.), a condensed tannin-containing legume, is known to reduce alfalfa pasture bloat in mixed stands. Experiments were conducted in 2010 to 2012 at Lethbridge, AB, using two sainfoin/cultivar AC Blue J alfalfa mixed pastures originally seeded as 50:50 mixes in 2008 and rotationally grazed by steers (Bos taurus). New sainfoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 34 publications
(52 reference statements)
0
35
1
1
Order By: Relevance
“…In another 3-yr study to compare incidence of bloat, ruminal fermentation, and feed intake of steers grazing alfalfa and mixed alfalfasainfoin pastures showed that inclusion of 35% sainfoin in mixed alfalfa-sainfoin pastures reduced but did not eliminate bloat (Wang et al, 2006). In a 3-yr grazing study, Sottie et al (2014) observed that bloat incidence increased from 5 to 43 and from 1 to 48 when the percentage of sainfoin was reduced from 29 to 7% and from 28 to 5% in sainfoin-alfalfa mixture, respectively. The CT content in forage mixtures used in these studies all exceeded 1.0 mg kg -1 DM.…”
Section: Frothy Bloatmentioning
confidence: 99%
See 3 more Smart Citations
“…In another 3-yr study to compare incidence of bloat, ruminal fermentation, and feed intake of steers grazing alfalfa and mixed alfalfasainfoin pastures showed that inclusion of 35% sainfoin in mixed alfalfa-sainfoin pastures reduced but did not eliminate bloat (Wang et al, 2006). In a 3-yr grazing study, Sottie et al (2014) observed that bloat incidence increased from 5 to 43 and from 1 to 48 when the percentage of sainfoin was reduced from 29 to 7% and from 28 to 5% in sainfoin-alfalfa mixture, respectively. The CT content in forage mixtures used in these studies all exceeded 1.0 mg kg -1 DM.…”
Section: Frothy Bloatmentioning
confidence: 99%
“…Like all other tannin‐containing plants, CTs are synthesized by a chloroplast‐derived organelle, the tannosome, and stored in vacuoles within the plant cell. In sainfoin there is an even distribution of tannin cells throughout the plant, a characteristic that differs from other tannin‐containing fodder legumes (Skadhauge et al, 1997). It has been shown that the compositions of sainfoin CTs vary with species, accessions, and growth stage and are composed of procyanidins (catechin + epicatechin; PC) and prodelphinidins (gallocatin + epigallocatechin; PD) (Koupai‐Abyazani et al, 1993a, 1993b; Leeds et al, 1995).…”
Section: Compositions Of Phenolic Compounds and Condensed Tannins In mentioning
confidence: 99%
See 2 more Smart Citations
“…Sainfoin can be grown as a monoculture or in mixtures with perennial grasses or alfalfa (Frame et al., ; Goplen et al., ; Hayot‐Carbonero, Mueller‐Harvey, Brown, & Smith, ). When sainfoin is grown in a mixture with alfalfa, it has been shown to reduce bloat incidence in beef cattle relative to the grazing of pure alfalfa (Malisch et al., ; Sottie et al., ).…”
Section: Introductionmentioning
confidence: 99%